2023
DOI: 10.1055/s-0043-1774783
|View full text |Cite
|
Sign up to set email alerts
|

The Intersection of Social Determinants of Health and Post-stroke Aphasia Outcomes: A Need for Intersectional Analysis

Elizabeth Evans,
Molly Jacobs,
Charles Ellis

Abstract: Aphasia is a disorder that results from damage to portions of the brain that are responsible for language and can vary significantly by type and severity. Differences in aphasia outcomes are influenced by the social determinants of health (SDOH). The SDOH are structural, environmental, and personal determinants that influence health outcomes. Intersectionality, or how one's social and political identities interact to influence individual life outcomes and/or advantage in our society, provides a way to examine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…Next, Centeno (2024) describes intersectional LPAA-based strategies, grounded in personal storytelling, to collect the input that can inform culturally responsive intervention in ethnosocially diverse aphasia caseloads in the United States. Finally, Evans et al (2024) propose a socioecological model to evaluate the impact of intersecting individual, environmental, and structural determinants of health on aphasia outcomes, especially in vulnerable populations.…”
Section: )mentioning
confidence: 99%
“…Next, Centeno (2024) describes intersectional LPAA-based strategies, grounded in personal storytelling, to collect the input that can inform culturally responsive intervention in ethnosocially diverse aphasia caseloads in the United States. Finally, Evans et al (2024) propose a socioecological model to evaluate the impact of intersecting individual, environmental, and structural determinants of health on aphasia outcomes, especially in vulnerable populations.…”
Section: )mentioning
confidence: 99%
“…In previous work we have suggested that any exploration of disparities in aphasia outcomes must carefully explore not only the SDOH but also studies designed with an intersectional lens of inquiry [ 18 ]. Intersectional approaches are utilized to explain how differing lived experiences translate into differences in clinical outcomes [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Intersectional approaches begin with careful consideration of childhood and how the early lived experience translate synergistically over to time and the influence of any geographic inequities that impact health over during the lifespan [ 20 ]. Most previous work in aphasia examining the association between social determinants and aphasia impairment have not evaluated the SDOH through an intersectional framework despite evidence that the SDOH often work synergistically to impact health outcomes [ 18 ].…”
Section: Introductionmentioning
confidence: 99%